A Building Ideal Concept Of Application Principles Good Faith in Agreement Law (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2022)
Suitable faith arrangements should be formulated as "the attitude or behavior of holding fast to the agreement to give the opponent what is his right and not looking for loopholes to break away from what has been agreed based on propriety and rationality. Standards used in objective good faith are objective standards that refer to an objective norm. The parties' behavior towards the agreement must be tested based on unwritten objective norms that develop in society. The norm is said to be objective because the behavior is based on the parties' assumptions. However, the behavior must be by the general assumption of good faith. The third function of good faith is the function of limiting and eliminating. Some pre-war legal experts argued that good faith also served this function. They teach that a specific agreement or a statutory provision regarding the contract can be set aside if, since the contract was made, the situation has changed so that the contract implementation creates injustice. Under such circumstances, contractual obligations can be limited or eliminated based on good faith. This study uses a normative juridical method. Namely, the provisions of the legislation must be carried out by what is stated in the legislation. This normative juridical method refers to research that leads to the philosophical basis of the contract, especially the philosophical basis of the existence of the doctrine of good faith.